The Prayer of Jesus on the Cross - Zawadzki, Ryszard (Verbum Vitae, 2012)
The Passion Narratives in Synoptic Gospels present Jesus on the cross not only as a Messias patiens, but also as a Messias orans. This article constitutes an attempt to show a synoptic picture of the Crucified who prays. In the first part of the article we focus on the nonverbal dimension of Jesus’ prayer on the cross, e.g. on the posture of his body forced by the means of execution and on his laud, inarticulate cry of the agony. In the second part, the subject of the analysis becomes three of seven “last words of Jesus”, that assume the form of prayer: Luc 23,34a; Mt 27,46; Luc 23,46.